Vascular extracellular signal‐regulated kinase mediates migraine‐related sensitization of meningeal nociceptors. Issue 6 (17th June 2013) - Zhang, XiChun; Kainz, Vanessa; Zhao, Jun; Strassman, Andrew M.; Levy, Dan
<x xml:space="preserve">Abstract</x> Objective To examine changes in the response properties of meningeal nociceptors that might lead to migraine pain and examine endogenous processes that could play a role in mediating them using a clinically relevant model of migraine triggering, namely infusion of the nitric oxide (NO) donor nitroglycerin (NTG). Methods Single‐unit recordings made in the trigeminal ganglion of rats were used to test changes in the activity and mechanosensitivity of meningeal nociceptors in response to administration of the migraine trigger NTG or another NO donor S‐nitroso‐N‐acetyl‐DL‐penicillamine (SNAP) at doses relevant to the human model of migraine headache. Immunohistochemistry and pharmacological manipulations were used to investigate the possible role of meningeal vascular signaling in mediating the responses of meningeal nociceptors to NO. Results Infusion of NTG promoted a delayed and robust increase in the mechanosensitivity of meningeal nociceptors, with a time course resembling the development of the delayed migraine headache. A similar sensitization was elicited by dural application of NTG and SNAP. NTG‐evoked delayed meningeal nociceptor sensitization was associated with a robust extracellular signal‐regulated kinase (ERK) phosphorylation in meningeal arteries. Pharmacological blockade of meningeal ERK phosphorylation inhibited the development of NTG‐evoked delayed meningeal nociceptor sensitization. Interpretation The development of delayed mechanical sensitization evoked by the migraine trigger NTG is potentially of great importance as the first finding of a neurophysiological correlate of migraine headache in meningeal nociceptors. The arterial ERK phosphorylation and its involvement in mediating the NTG‐evoked delayed sensitization points to an important, yet unappreciated, role of the meningeal vasculature in the genesis of migraine pain. ANN NEUROL 2013;73:741–750